Tecnologia educativa para a abordagem de urgências neuropsiquiátricas na pessoa idosa atendida em unidade de pronto atendimento - Galindo Júnior, José Uilson Ferreira (2025)
Introduction: Population aging has led to a significant increase in mental health demands among the elderly, especially in urgent and emergency situations. In this context, Emergency Care Units (UPAs) are often the first point of care for elderly people with neuropsychiatric emergencies, such as anxiety disorders, delirium, depression, suicidal ideation, dementia, among others. However, the health professionals who work in these services often face difficulties in dealing with these cases properly, which highlights the need for more in-depth research on the subject. Objective: To map and analyze the main scientific evidence on the use of educational technologies to address neuropsychiatric emergencies in the elderly, as well as to develop an educational e-book with practical guidelines to improve the care provided to this population. Method: This is a methodological, qualitative, exploratory study developed in three stages. In the first stage, a scoping review was carried out to map the available scientific evidence on the main neuropsychiatric emergencies and the use of educational technologies aimed at the mental health of the elderly. In the second stage, a field study was conducted with semi-structured interviews with 15 health professionals from a UPA in the municipality of João Pessoa/PB. The data collected was analyzed using IRAMUTEQ software and subjected to content analysis. In the third stage, based on the findings of the previous stages, an educational e-book was produced for health professionals, containing practical guidelines for the management of neuropsychiatric emergencies in the elderly. Results: The difficulty in the early identification of neuropsychiatric symptoms stands out, resulting in inadequate approaches and prolonged patient stays in the unit. The absence of specific protocols and the lack of training were pointed out as factors that compromise clinical management, increasing the insecurity of professionals in managing these conditions. There is also a shortage of educational materials, which contributes to inconsistent clinical decisions and unnecessary referrals to hospital services. Work overload and the lack of specialized support were also highlighted as barriers to providing more humanized and resolutive care. Discussion: The need for continued training for professionals was highlighted, especially in the early recognition and appropriate management of neuropsychiatric conditions in the elderly. It was evident that investment in educational technologies can fill training gaps and support clinical decision-making, contributing to the construction of more qualified, humanized care centered on the elderly patient. The e-book developed, by bringing together fundamental concepts, flows and practical guidelines, is a strategic tool to support the ongoing education of professionals. Final considerations: The management of neuropsychiatric emergencies in the elderly remains a significant challenge in UPAs, where technical training and the provision of educational materials are strategies to improve the quality of care. The e-book developed represents a contribution to support professional practice, with the potential to strengthen patient safety, optimize care flows and promote more resolute and humanized care.